2009
DOI: 10.1021/jp808425k
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Nanoparticles with Magnetization and Luminescence

Abstract: The Fe 3 O 4 @LaF 3 :Ce 3+ -Tb 3+ bifunctional composite nanoparticles were fabricated with a facile layer-bylayer technology. To get these bifunctional nanocomposites, the as-prepared magnetic (Fe 3 O 4 ) and luminescent (LaF 3 :Ce 3+ -Tb 3+ ) nanoparticles were modified with polyelectrolyte to get positively charged and negatively charged surfaces, respectively. The nanocomposites were then obtained by absorbing the negatively charged LaF 3 :Ce 3+ -Tb 3+ @(PAH/PSS) 2 luminescent nanoparticles onto the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…11,31,32 DPA played a strong oxidizing role with luminol, and some drugs were capable of enhancing the CL reaction. 15 In the present study, the maximum CL in the presence and absence of thiram and aminocarb containing nitrogen appeared at a 610 nm, and a much higher CL peak was observed in the presence of thiram and aminocarb, indicating that Ru(II) is the luminophore. DPA is used as an oxidizing agent for generating Ru(bipy)3…”
Section: Reaction Mechanismsupporting
confidence: 51%
See 1 more Smart Citation
“…11,31,32 DPA played a strong oxidizing role with luminol, and some drugs were capable of enhancing the CL reaction. 15 In the present study, the maximum CL in the presence and absence of thiram and aminocarb containing nitrogen appeared at a 610 nm, and a much higher CL peak was observed in the presence of thiram and aminocarb, indicating that Ru(II) is the luminophore. DPA is used as an oxidizing agent for generating Ru(bipy)3…”
Section: Reaction Mechanismsupporting
confidence: 51%
“…[11][12][13] Yang and Zhang 14 have reported a flow-injection (FI)-CL method for the determination of uric acid in human serum based on the reaction of DPA with uric acid in an alkaline medium; it generates a strong CL signal with a detection limit (3σ) of 1.2 × 10 -7 mol L -1 . Yang et al 15 have reported an FI-CL method for amikacin sulfate in human serum based on its enhancement effect on a luminol-DPA CL system in an alkaline medium with a detection limit (3σ) of 1.9 × 10 -8 mol L -1 . Zhao et al 16 have reported another FI-CL method for gemifloxacin in pharmaceutical preparations and biological fluids based on a gemifloxacin-DPA CL reaction in a sulfuric acid medium sensitized by cetyltrimethylammonium bromide with a detection limit (3σ) of 7.3 × 10 -10 g mL -1 .…”
mentioning
confidence: 99%
“…During the past decades, magnetic nanoparticles [1,2], noble metal nanocrystals [3], quantum dots (QDs) [4][5][6][7], and other kinds of luminescent nanomaterials [8][9][10] have been successfully prepared and widely used in the biological and medical fields. Due to their novel optical properties, QDs are preferable to organic dyes for biotagging applications.…”
Section: Introductionmentioning
confidence: 99%
“…These formulations not only serve the purpose of being drug delivery vectors but also have applications in MRI imaging, 95 targeted thermosensitive chemotherapy, 96 magnetically targeted photodynamic therapy, 97 and fluorescent/luminescence imaging. 98 Yallapu et al developed water-dispersible SPIONs for hyperthermia, MRI, and drug delivery applications. SPIONs were prepared by precipitation of iron salts in the presence of ammonia and coated with β-cyclodextrin and a Pluronics polymer.…”
mentioning
confidence: 99%